2003
DOI: 10.1002/app.12652
|View full text |Cite
|
Sign up to set email alerts
|

Role of a chelating agent in the formation of polyaniline films on aluminum

Abstract: A chelating agent, alizarin, was used to pretreat an aluminum surface before the electrochemical synthesis of polyaniline. Alizarin had two main effects on the process: (1) it suppressed the hydrogen evolution reaction and increased the current efficiency and (2) it stabilized the open-circuit potential in a corroding environment, such as in 0.1M NaCl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
6
0
3
Order By: Relevance
“…Motheo et al, reported a chelation method to electropolymerize PANi films on Al surfaces using alizarin as a chelating agent [19,21,23]. An important finding of this work is that the method of chelation with alizarin suppressed hydrogen evolution in aqueous solutions and increased the current efficiency for the PANi deposition during the electropolymerization.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Motheo et al, reported a chelation method to electropolymerize PANi films on Al surfaces using alizarin as a chelating agent [19,21,23]. An important finding of this work is that the method of chelation with alizarin suppressed hydrogen evolution in aqueous solutions and increased the current efficiency for the PANi deposition during the electropolymerization.…”
Section: Introductionmentioning
confidence: 71%
“…An important finding of this work is that the method of chelation with alizarin suppressed hydrogen evolution in aqueous solutions and increased the current efficiency for the PANi deposition during the electropolymerization. It was also noted that the method works best with oxalic acid in the growth solution along with aniline [19,23]. However, these electrodes do not withstand transfer to nonaqueous solvent.…”
Section: Introductionmentioning
confidence: 96%
“…These chromate containing baths are aggressive to the environment and alternatives are necessary. Some of the potential alternative organic coatings for aluminium corrosion protection are those based on self-assembled monolayers (SAM) [1][2][3][4][5][6][7][8][9], conducting polymer films [10][11][12][13][14][15][16][17][18][19][20][21] and, in recent years, SAM=polymer double films [22].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in some cases the deposition of PAni by casting solution is the more viable method, in some cases. Despite this, fewer reports describe the deposition of polyanilines (PAni and POMA) on aluminum alloys, such as AA-7075-T6 [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%